Transfer matrix solution to free-field response of a multi-layered transversely isotropic poroelastic half-plane - Liang, Jianwen; Wu, Mengtao; Ba, Zhenning; Lee, Vincent W. (Soil dynamics and earthquake engineering (1984), 2020)
Free-field response of a layered medium is of fundamental important for studying wave propagation and SSI problems, however, few researches have been conducted on this subject. In this paper, a transfer matrix method is presented to solve the free-field motion of a multi-layered transversely isotropic (TI) poroelastic half-plane subjected to incident plane qP1-, qP2- and qSV-waves. First, the displacement and stress expressions are obtained by solving the governing differential equations for a TI poroelastic medium. Then, the transfer matrices are derived by the continuity of tractions and displacements at layer interfaces, a transfer matrix solution for free-field response of the multi-layered TI poroelastic half-plane under obliquely incident seismic waves is presented. The free surface of the stratified system can be considered either completely drained or undrained. The accuracy of theoretical formulations is verified through comparison with existing layered TI as well as homogeneous saturated medium models. Numerical examples of varying key parameters are given out to evaluate the ground seismic responses. Results show that both anisotropy and porous property of medium have very important effect on the resonance frequency and peak amplitude. Meanwhile, due to the filtering and amplification mechanism of soil layer to ground motion, thicker layers have a more obvious amplification effect on low-frequency components and a certain "isolation" effect on high-frequency components. •Transfer matrix method for free-field response of a multi-layered TI poroelastic half-plane is proposed.•Free surface is considered either completely drained or undrained condition.•The method is validated by existing layered TI and homogeneous saturated medium models.•Displacement responses of layered system for different parameters are given.